ANALISIS PERBEDAAN PENAMPANG SEISMIK ANTARA HASIL PENGOLAHAN STANDAR DENGAN PENGOLAHAN PRESERVED AMPLITUDE - Mukaddas, Abdul (MEKTEK, 2005)
Landslide is one of the most types of slope movements of soil ock often occur in Indonesia and resulting in damages such as in agriculture land, highways, structures and even casualties. From the researches landslides often take place on the rainy season,as well as when the rain is falling or after the rain stopped. This research will be done in two phases. First phase is a numerical modeling to simulate and predict slope hidrological behavior in respon to rainfall. The rainfalls applied for modeling are high and low intensity that are ï‚£ 70 mm/hour and 20 mm/day respectively some hours until days. The rainfall modeling results is used as the data for next phase that is slope stability analysis. Slope stability will be analiyzed at the initial condition, when raining and after the rain stopped. This research results the decreased of slope stability caused by the rain depends on the intensity and duration of the rain. The research obtains that the rain intensity of 70 mm/hour is the most potential cause to trigg the landslide than goes of 20 mm/day, 30 mm/hour and 50 mm/hour